METHODOLOGICAL ANALYSIS OF ORIENTALIST VIEWS ON EXISTENCE OF SURAH AL-FATIHAH IN THE QUR'AN AND ITS IMPLICATIONS FOR WESTERN SCHOLARSHIP - Moh. Nurun Alan Nurin PK (Halaqah: Journal of Multidisciplinary Islamic Studies, 2025)
The rejection of Surah Al-Fatihah as part of the Quran does not only come from Western scholars but also from Muslim scholars. This becomes interesting to study and analyze further because Al-Fatihah, which is notably the foremost surah in the Quran, is not exempt from controversy and conflicting opinions, not only from Western scholars but also from Eastern scholars.The data sources used consist of primary sources obtained from the works of several Orientalists and secondary sources obtained from previous research. The results of this study indicate that, firstly, from the perspective of Orientalists, in this case, Arthur Jeffery, Surah Al-Fatihah is a surah that is not connected to the other surahs (it was not originally part of the text). According to Jeffery, Al-Fatihah is a composed prayer like other sacred books in other religions. Secondly, this argument is based on a hypothesis that Al-Fatihah has been influenced by various foreign languages such as Ethiopian, Aramaic, Hebrew, Syriac, Ancient Greek, Persian, and others. Consequently, the vocabulary in the Quran adopts terms from Judaism, Christianity, and other cultures. Based on the discourse on the controversy of Surah Al-Fatihah above, thirdly, Jeffery's study has provided an interesting historical reality about Surah Al-Fatihah, but his evidence has not been able to refute the existing fact that Al-Fatihah is still believed to be part of the Quran.